EDUKASI SANITASI TOTAL BERBASIS MASYARAKAT (STBM) UNTUK PENCEGAHAN PENYAKIT BERBASIS LINGKUNGAN DI DESA PENDUNG TENGAH, KABUPATEN KERINCI - Naser, Mhd. Izzan; Sulistyorini, Lilis; Putri, Fitria Eka; Azizah, R. (VISIKES, 2025)
Background: Inadequate sanitation is a key contributor to the spread of diseases such as diarrhea, skin infections, and acute respiratory infections (ARI), particularly in rural areas like Pendung Tengah Village, Kerinci Regency. Limited knowledge and unfavorable attitudes toward hygiene exacerbate these conditions. Objective: This study aims to assess the impact of Community-Based Total Sanitation (STBM) education on improving knowledge and attitudes. Aim: To evaluate the effectiveness of STBM education in enhancing sanitation-related awareness and behavior among housewives. Method: A pre-experimental one-group pretest-posttest design was conducted involving 30 randomly selected housewives, using a structured questionnaire and paired t-test analysis. Result: Significant increases were observed in knowledge (from 6.10 to 9.00) and attitudes (from 7.23 to 9.13), with a p-value of 0.000 (< 0.05). Conclusion: STBM education effectively improves sanitation knowledge and attitudes, though sustained efforts are needed for long-term impact. The study hypothesizes that STBM education significantly enhances household sanitation behavior. The novelty lies in empowering rural housewives as key agents of change, showing that targeted, behaviorbased education can be impactful and scalable in low-resource settings.